Carcass characteristics, palatability, and shelf life on beef finished on selected feeding regimes - Allen, Dell M.; Hunt, Melvin C.; Kropf, Donald H.; Chen, V.; Corte, O.; Gutowski, G.H.; Harrison, A.R.; Kuntapanit, C.; Thomas, J.D.; McCurry (Smith), M.E.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station, 2011)
This report terminates a 3-year study and includes data from this past year. Previous results were reported in the 1976 and ’77 Cattlemen’s Day Report.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Carcass; Palatibility; Shelf life